The poetics of M. Tsvetaeva's literary essays and the traditions of modernist criticism in the early 20th century - V.N. Krylov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper studies the poetics of Marina Tsvetaeva's literary essays. It deals with such themes as M. Tsvetaeva's standpoint in the literary life of the 1910s, her outlook on nature and the criticism objectives, relationship of the critic and the poet, and implementation of theoretical views in critical practice. The study has been performed in order to identify the links between M. Tsvetaeva's patterns and literary methods and the traditions of Russian modernist criticism of the early 20th century. To achieve the above-said aim, structural, semiotic, and biographical methods have been used along with the elements of linguistic analysis of the literary and critical text. Both M. Tsvetaeva's essays and her correspondence have served as the sources of information. The paper provides a number of examples to argue about M. Tsvetaeva's commitment to literary criticism, as well as her negative attitude to formal approach, vulgar and biographical, historical and genetic research methods of literary creativity. Her critical work is associated with the category of responsibility that was important for M. Tsvetaeva. Detours on aesthetic themes are typical of the poetics of her essays. Having analyzed M. Tsvetaeva's essays, we have concluded that the author's spirit is strongly manifested in her criticism. Its peculiarity is expressed in an offensive tone of the indisputable and irresistible confidence. M. Tsvetaeva's essays evolve a number of trends in the modernist criticism of the early 20th century (she introduces in the text her memoirs, personal experience, and the emotions she got from a piece of art). Another form of M. Tsvetaeva's communication with the traditions of modernism is a semantic and structural stress on the importance of other people's texts, a special role of the poetic word in the essay, rhetoric of oppositions, and appeal to the possibilities of the genre of parallels. The findings are essential for the study of poetics criticism of the 20th century and works by M. Tsvetaeva.